Microstructure of Layered Porous TiAl Composite Sheet Synthesized by Reacted Sintering - LI Xue-wen; LIU Gang; SUO Zhuan-xia; WEI Bo-xin; FANG Wen-bin (Journal of Harbin University of Science and Technology)
In this paper, pure Ti foil, pure Al powder and pure Nb powder are used as raw materials Firstly, AlNb composite foil was prepared by powder metallurgy process, and then layered porous TiAl alloy sheet is prepared by foil metallurgy The results show that after vacuum hot pressing, there is no new phase in the Ti/AlNb composite sheet, and the combination of Ti foil and AlNb composite foil is mechanically combined, and the thickness of the sheet is uniform The thin plate after step heat treatment is composed of six phase layers of Al3Nb, TiAl3, TiAl2, TiAl, AlNb2 and Ti3Al, wherein the TiAl phase layer has a thickness of about 100 μm, the Ti3Al phase layer has a thickness of about 12 μm, and the (Ti, Nb) Al3 phase layer thickness It is about 80 μm and the thickness of the TiAl2 phase layer is about 2 μm AlNb2 is distributed in the (Ti, Nb)Al3 phase layer, and irregularly distributed pores are formed in the (Ti, Nb)Al3 phase layer